CONVIVÊNCIA ENTRE CUIDADOR FAMILIAR E IDOSA COM DOENÇA DE ALZHEIMER NO DOMICÍLIO - Anjos, Karla Ferraz dos; Santos, Vanessa Cruz; Silva, Jaine Kareny da; Andrade, Lorrana Lorrana Alves Almeida Dantas D’; Santa Rosa, Darci de Oliveira; Boery, Rita Narriman Silva de Oliveira (Revista Brasileira de Saúde Funcional, 2019)
Não há necessidade